The Effects Of Entrepreneurial Leadership, Intellectual Capital, Technology Capability, And Government Support Towards Strategic Agility And Smes Competitiveness In Indonesia - Sari, Synthia Atas (2022)
Although small-medium enterprises (SMEs) importance, nevertheless, the uncertainties and disruptions caused by the pandemic further exacerbated the challenges and agility of SMEs. Previous studies showed contrasting debates regarding the origins of SMEs' competitiveness; however, many themes were still unexplored, especially in understanding the agility and competitive level of SMEs in industry 4.0. This study investigated four key variables, namely entrepreneurial leadership, intellectual capital, technology capability, and government support, that are predicted to influence strategic agility and competitiveness of SMEs from an individual, organisational, and institutional lenses based on upper-echelon theory and dynamic capability theory. The descriptive nature of this thesis led to the adoption of a quantitative research methodology, and a survey method was conducted to gather information from 190 top-level management/owners of SMEs. Partial least squares-structural equation modelling (PLS-SEM) was used for data analysis, and two key findings emerged. First, the four key variables individually had a significant positive impact on SMEs’ strategic agility. Secondly, strategic agility significantly mediated the intellectual capital and government support, while entrepreneurial leadership and technology capabilities did not mediate SMEs competitiveness.